Content Analysis of Institutional Policies on the Use of AI in Top HEIs - Sotto, Jose Cris O.; Tamayo, Josan D.; Vicente, Clarissa P. (Future Science / FSH-PH Publications, 2025)
The unprecedented rise of generative artificial intelligence (AI) in 2022 has compelled leading universities to articulate formal policies governing its pedagogical and research applications. Yet coherent guidance for higher education systems—particularly in the Global South—remains underdeveloped. This study undertook a thematic analysis of AI policies issued by the top 50 institutions in the Times Higher Education World University Rankings 2023, employing Chan’s (2023) pedagogical, governance, and operational dimensions as analytic lenses. The analysis demonstrates a global convergence around AI’s pedagogical utility and research-enhancing potential, tempered by robust institutional commitments to academic integrity, responsible deployment, and the ethical management of AI-generated content. Universities are also investing in interdisciplinary AI initiatives, cultivating industry partnerships, and adopting differentiated approaches to instructor autonomy in regulating classroom AI use. These insights offer a critical foundation for Philippine higher education institutions seeking to articulate contextually grounded, ethically defensible, and future-oriented approaches to AI governance.